SMART CITY IN THE CONTEXT OF BLOCKCHAIN TECHNOLOGY DEVELOPMENT: Array - Boyko, V.; Vasilenko, M.; Novikov, V.; Rachuk, V. (Municipal economy of cities (Technical science), 2021)
The article analyzes how the use of digital technologies through working databases improves the infrastructure of the "smart city", improving the integrated information environment of the" smart city", synchronizing information between databases. The general benefits of digital transformation, the lack of trivial application protection, generally accepted approaches to data protection, and the use of blockchain to protect data in the smart city ecosystem are considered. It is shown that with certain urban initiatives and with a tight link between information systems within a "smart city", it is possible to organize services that do not require initial user participation at all. Among the requirements for successful digital transformation, there are requirements for developing a strategy, team motivation, adapting staff to new teams, and introducing new technologies specific to the urban environment. In particular, there are increased requirements for the speed of response, that is, how quickly the smart city system can bring the necessary services to the market and how quickly it allows them to comply with the legislation. Attention is drawn to the following generally accepted approaches to data protection: data protection in the application using a strong cryptographic system with symmetric keys, data protection in the application using a strong cryptographic system with asymmetric keys, with possible participation of the customer, flourishing data exchange. The use of cryptographic systems with blockchain technologies allows you to create new strategies for privacy and speed of information exchange and management. An important component of such a system is the "key", which represents the first link in the blockchain chain and can be stored outside the system and used for various checks in the activities of divisions of the apparatus of local and municipal enterprises of the city. From a scientific point of view, the use of blockchain technologies in the future leads to the need for interdisciplinary research and their application for various applications to determine the strategies and social consequences of such application.